Dataset Digital Forensics in Law (2012-2022): A Comprehensive Lens.org Data Analysis - Siswapranata, Fadiana Zahra; Multazam, Mochammad Tanzil; Rositasari, Dewi (Proceedings of The ICECRS, 2023)
This study presents a comprehensive analysis of scholarly articles in "Digital Forensic and Forensic Sciences" within the Law subject matter from 2012 to 2022, using data from Lens.org. Filtering 21,619 documents resulted in 1,566 pertinent articles, revealing Universite de Lausanne as the top-contributing institution and Eoghan Casey as the most prolific author with 36 articles. A peak in 2019 marked heightened scholarly activity, predominantly in Computer Science. The United Kingdom emerged as the most active region, and Elsevier as the leading publisher. This analysis sheds light on the trends, key contributors, and focal areas in digital forensic research within the legal domain. Highlights: Law-centric focus: The study delves into digital forensics within the legal realm, narrowing down scholarly articles to a pertinent subset. Regional prominence: Highlighting the United Kingdom as a hub of activity underscores regional disparities in contributions to this field. Author and institutional contributions: Universite de Lausanne and Eoghan Casey emerge as pivotal contributors, emphasizing their influence on this niche area of study. Keywords: Digital Forensic, Forensic Sciences, Law, Scholarly Articles, Trends